2008
DOI: 10.1016/j.virusres.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

The alternative splicing factor hnRNP A1 is up-regulated during virus-infected epithelial cell differentiation and binds the human papillomavirus type 16 late regulatory element

Abstract: Human papillomavirus type 16 (HPV16) infects anogenital epithelia and is the etiological agent of cervical cancer. We showed previously that HPV16 infection regulates the key splicing/alternative splicing factor SF2/ASF and that virus late transcripts are extensively alternatively spliced. hnRNP A1 is the antagonistic counterpart of SF2/ASF in alternative splicing. We show here that hnRNP A1 is also up-regulated during differentiation of virus-infected epithelial cells in monolayer and organotypic raft culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…In addition, it has been shown that hnRNP A1 expression is enhanced during human papilloma virus and HIV-1 infections (43,44). We verified whether hnRNP A1 expression was increased in productively infected T cells by transfecting CD4/CXCR4ϩ Jurkat CE6.1 T cells with the wild-type proviral HIV-1 DNA construct pNL4-3 and assessing expression levels between 0 and 12 days post-transfection.…”
Section: Increased Expression and Cytoplasmic Accumulation Of Hnrnp Amentioning
confidence: 81%
“…In addition, it has been shown that hnRNP A1 expression is enhanced during human papilloma virus and HIV-1 infections (43,44). We verified whether hnRNP A1 expression was increased in productively infected T cells by transfecting CD4/CXCR4ϩ Jurkat CE6.1 T cells with the wild-type proviral HIV-1 DNA construct pNL4-3 and assessing expression levels between 0 and 12 days post-transfection.…”
Section: Increased Expression and Cytoplasmic Accumulation Of Hnrnp Amentioning
confidence: 81%
“…Cells of the non-tumor subclone W12E (clone 20863), when maintained at low passage (P Ͼ 17), contain around 50 to 100 episomal copies of the HPV16 genome (26,35). W12E cells can be induced to differentiate to keratinocytes that express markers of terminal differentiation (36), viral late mRNAs and late proteins (10) by culturing to high density in the presence of 1.88 mM Ca 2ϩ . Previously, we showed that a subset of SRSF proteins, including SRSF1, -2, and -3, were upregulated upon differentiation of W12E cells (24).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the heterogeneous nuclear ribonucleoproteins (hnRNP) isoforms A1 and A2 as negative splicing regulators, already known to be increased during epithelial cell differentiation and involved in HPV16 gene late expression (27), pronounced exon exclusion was only detectable when both splicing factors were knocked down, whereas reduction of only hnRNPA2 showed a moderate effect on exon retention (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%